Lightwear: An Exploration in Wearable Light Therapy - Profita, Halley P; Roseway, Asta; Czerwinski, Mary (In Proceedings of TEI 2015, 2015)
We present “Lightwear”, a series of garment-based, lightweight, light-emitting wearables designed to administer light therapy for on-the-go treatment of Seasonal Affective Disorder (SAD). Bright Light Therapy (BLT) has been used to treat SAD for more than 25 years. While light boxes continue to serve as the predominant method of treatment, it often requires a user to sit at a dedicated location for a sustained period of time (30-60 minutes), rendering therapy inconvenient and resulting in unsatisfactory compliance rates. To date, there have been few successful products developed for wearability and portability to ease the uncomfortable nature of light box treatment. However, new low-profile, light-emitting sources yield opportunities for less cumbersome textile integration and wearability. We explore the integration of light into textile substrates that focus on fashion-forward wearables which can, in turn, address BLT efficacy, usability, and convenience.